Acting, interacting, enacting: Representing medical practice in theatre performance - Hazel, Spencer (Academic Quarter | Akademisk kvarter, 2015)
This study followed the rehearsals of a 2014 Copenhagen theatre production of Margaret Edson’s play WIT. The play depicts the palliative care provision of a woman diagnosed with advanced ovarian cancer, with an important theme of the narrative centering around the dehumanizing practices that result from professional medical treatment of the body, rather than of the person. I adopt an interaction analytic approach to investigate how theatre practitioners develop representations of interaction in clinical environments. The article introduces one practice from the theatre rehearsal setting – doing notes – which forms a framework within which members reflect on their performances, and discuss possible modifications to be taken up on later occasions. This is argued to be a useful practice that may prove beneficial to other professional settings, such as in heathcare provision.